The novel brassinosteroid analog BR4848 inhibits angiogenesis in human endothelial cells and induces apoptosis in human cancer cells in vitro - Rárová, Lucie; Sedlák, David; Oklestkova, Jana; Steigerová, Jana; Liebl, Johanna; Zahler, Stefan; Bartůněk, Petr; Kolář, Zdeněk; Kohout, Ladislav; Kvasnica, Miroslav; Strnad, Miroslav (The Journal of steroid biochemistry and molecular biology, 2018)
We report the synthesis and detailed biological study of the synthetic brassinosteroid analog 2α,3α-dihydroxy-6-oxo-5α-androstan-17β-yl N-(tert-butoxycarbonyl)-D,L-valinate (BR4848). The panel of cancer cell lines was used for characterization of its antiproliferative activity, yet had no adverse effects in normal human fibroblasts. In HeLa cells, BR4848-induced apoptosis was accompanied by increase of apoptotic subG1 cells, PARP-1 and caspase-7 fragmentation, downregulation of Bcl-2 and Mcl-1, an increase in caspase activity and G2/M phase cell cycle arrest. Antiproliferative properties of BR4848 were exhibited by inhibition of phosphorylation of Akt, Erk1/2 and FAK. Furthermore, the developed analog exhibited in vitro antiangiogenic activity in human umbilical vein endothelial cells (HUVECs). BR4848-induced apoptosis accompanied with G2/M arrest was detected in endothelial cells. BR4848 also inhibited adhesion, tube formation and migration of endothelial cells by inhibition of FAK, Erk 1/2, CDK5, VEGFR2, TNFα-stimulated production of IL-6, angiopoietin-2 and Jagged1. Finally, BR4848 did not modulate the activity nor nuclear translocation of any of the steroid receptors (ERα, ERβ, AR, MR and PR) included in reporter cell-based assays, which excludes the genomic activity of steroid receptors as a contributing factor to the observed biological activities of BR4848.
Keywords: signální transdukce; Phosphorylation; Signal Transduction; inhibitory angiogeneze; techniky in vitro; Humans; Tumor Cells, Cultured; fosforylace; Angiogenesis; Cell Cycle Checkpoints; lidé; proliferace buněk; Human Umbilical Vein Endothelial Cells; apoptóza; nádorové buňky kultivované; Neovascularization, Pathologic; brassinosteroidy; Brassinosteroid analog; endoteliální buňky pupečníkové žíly (lidské); Cell Proliferation; Angiogenesis Inhibitors; Neoplasms; HUVEC; Brassinosteroids; kontrolní body buněčného cyklu; In Vitro Techniques; nádory; Cancer cell lines; patologická angiogeneze; Apoptosis